A Service-Oriented Component-Based Framework for Dynamic Reconfiguration Modeling Targeting SystemC/TLM. (3rd August 2021) - Allem, Khaled; Bourennane, El-Bay; Khelfaoui, Youcef
Abstract : To deal with the complex design issues of Dynamically Reconfigurable Systems-on-Chip (DRSoCs), it is extremely relevant to raise the abstraction level in which models are expressed. A high abstraction level allows great flexibility and reusability while bypassing low-level implementation details. In this context, model-driven engineering (MDE) provides support to build and transform precise and structured models for a particular purpose at different levels of abstraction. Indeed, high-level models are successively refined to low-level models until reaching the executable ones. Thus, this paper presents an MDE-based framework for DRSoCs design enabling the transformation of UML/MARTE specifications to SystemC/TLM implementation. To achieve a high degree of expressiveness for modeling dynamic reconfiguration, we use a suitable software engineering approach based on service-oriented component architecture. Since MARTE does not cover the common features of dynamic reconfiguration domain and service orientation concepts, new stereotypes are created by refinement to add missing capabilities to the profile. Likewise, SystemC does not provide native support for dynamic reconfiguration, thus leading us to adopt a design pattern based solution for DRSoCs implementation in compliance with standards. The proposed framework is validated through a reconfigurable active 3-way crossover case study in which we demonstrate the practicability of the approach by gradual model transformations with reduced implementation effort and significant design productivity gain.